Comparative renoprotective effect of Tamarix dioica leaf extracts and metformin against acetaminophen-induced renal toxicity in Swiss albino mice: Novel insights on renoprotection and therapeutic potential: Renoprotective effects of Tamarix dioica - Albalawi, Aishah E; Aggad, Waheeb S.; Alharbi, Fawiziah Khalaf Rashed; Almuhimed, Rawabi Mohamed; Alhuwaymil, Zamzam; Almohaimeed, Hailah M.; Mohammedsaleh, Zuhair M.; Alhasani, Reem Hasaballah; Alsharif, Ifat; Al-Abbas, Nouf S.; A Shaer, Nehad.; Mavromatis, Charalampos; et al. (Cellular and Molecular Biology, 2025)
Nephrotoxicity is characterized by the adverse effects on kidney function caused by various substances, including hazardous chemicals and drugs. This study aimed to investigate the neuroprotective properties of aqueous, methanolic, and ethanolic extracts of Tamarix dioica leaf against acetaminophen-induced kidney damage and compare their efficacy with metformin, a known neuroprotective agent. Thirty-six albino mice were randomly divided into six groups, including a standard control group, an acetaminophen-toxified group, a positive control group treated with metformin (at a dose of 200 mg/kg body weight), and three experimental groups treated with aqueous, methanolic, and ethanolic T. dioica extracts (at a dose of 400 mg/kg body weight each). The neuroprotective potential of the T. dioica extracts was assessed by evaluating hematological markers, electrolyte levels (Na+, K+, Cl-), antioxidant enzymes (CAT, SOD, MDA), renal function tests (urea and creatinine), and toxicity markers (SGOT and SGPT). Additionally, histopathological analysis was conducted to observe any pathological changes in kidney tissues stained with hematoxylin and eosin. The results demonstrated that the T. dioica leaf extracts effectively restored all the indicators and antioxidant enzyme levels to normal, significantly differing from the elevated levels observed in the acetaminophen control group (p < 0.05). Furthermore, histopathological examination revealed regeneration of glomeruli and renal tubules in the stained tissues. These findings suggest that T. dioica leaf extracts can potentially mitigate acetaminophen-induced nephrotoxicity.